2012
DOI: 10.3842/sigma.2012.071
|View full text |Cite
|
Sign up to set email alerts
|

Conservation Laws, Hodograph Transformation and Boundary Value Problems of Plane Plasticity

Abstract: Abstract. For the hyperbolic system of quasilinear first-order partial differential equations, linearizable by hodograph transformation, the conservation laws are used to solve the Cauchy problem. The equivalence of the initial problem for quasilinear system and the problem for conservation laws system permits to construct the characteristic lines in domains, where Jacobian of hodograph transformations is equal to zero. Moreover, the conservation laws give all solutions of the linearized system. Some examples … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(49 citation statements)
references
References 21 publications
(35 reference statements)
1
45
0
3
Order By: Relevance
“…Conservation laws have been successfully used to solve many problems in mathematics and mechanics. Summary of results and solved problems from various fields of mechanics can be found in [1][2][3][5][6][7].…”
Section: Figmentioning
confidence: 99%
“…Conservation laws have been successfully used to solve many problems in mathematics and mechanics. Summary of results and solved problems from various fields of mechanics can be found in [1][2][3][5][6][7].…”
Section: Figmentioning
confidence: 99%
“…Taking into account solutions (19), (21), (22), we can express operator Y 1 in terms of r, ϕ, θ c , σ. Namely, for the higher sing solution tan θ p = η/ξ we have:…”
Section: θ 1 : Quasi-scale Transformationmentioning
confidence: 99%
“…In [15,16] it was shown that the method of CL permits to avoid the restriction on the Jacobian of hodograph transformation, usually using to solve hyperbolic quasilinear PDEs. The existence of two families of real characteristics has played a significant part and the analogue of Riemann-Green function for quasilinear system has been constructed.…”
Section: Introductionmentioning
confidence: 99%